2013
DOI: 10.1016/j.jmii.2012.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis in children without underlying heart disease

Abstract: Over one-third (35.4%) of cases of IE in children occurred in patients without pre-existing cardiac disease. Early identification of these patients is critical and requires a high index of suspicion. The pathogenesis of IE in previously healthy individuals is still uncertain, but previous skin infection or dental problems may contribute to potential risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
4
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 26 publications
8
49
4
2
Order By: Relevance
“…This finding is in agreement with previous studies that made a diagnosis of IE in approximately 20% of their cases without risk factors potentially associated with this severe infectious disease [9,23,24]. In the absence of predisposing cardiac disease, IE involved mainly mitral valce, whereas pulmonary valve was involved frequently in the presence of CHD.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in agreement with previous studies that made a diagnosis of IE in approximately 20% of their cases without risk factors potentially associated with this severe infectious disease [9,23,24]. In the absence of predisposing cardiac disease, IE involved mainly mitral valce, whereas pulmonary valve was involved frequently in the presence of CHD.…”
Section: Discussionsupporting
confidence: 92%
“…The youngest patient previously described was 2 years old. [10][11][12][13][14][15][16] In this case, the patient underwent a lotus and water birth. Although unusual neonatal infections have been reported with water births in the past, including, among others, Legionella pneumonia and Haemophilus sepsis, 17,18 larger studies have shown that there is no significant increased risk of subsequent neonatal infections in newborns who underwent water births.…”
Section: Discussionmentioning
confidence: 95%
“…CoNS ranked as the 3 rd most common pathogen in 5 out of 7 studies. Two studies found Candida albicans to be the 2 nd and 3 rd most common pathogen respectively, [25,26] while cases of Enterococcus spp were also reported. Injectable drug user(s) (IDUs): Four retrospective cohort studies (N. America: 2, Asia: 1, Europe: 1) comprising a total of 580 cases examined the characteristics of IE among populations of IDUs.…”
Section: Special Populationsmentioning
confidence: 99%